2011
DOI: 10.1002/nau.21186
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of systematized behavioral modification program for nocturia: A prospective study

Abstract: A single SBMP was sufficient for treating most of the patients with NPU and reinforcement SBMP was effective in some patients. Moving from two to one rises at night may significantly reduce bother and this may explain quality of life improvements rather than any decrease in amount voided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The recommended treatment of nocturia in older adults includes optimizing therapy for fluid overload conditions such as congestive heart failure and diabetes mellitus and treating underlying bladder or prostate etiologies with antimuscarinics or alpha‐blockers, but such agents cause adverse events and further enhance the risk of falls, fractures, and mortality in older individuals with nocturia . Multicomponent behavioral or lifestyle interventions to improve nocturia, mostly focused on fluid restriction, preemptive voiding, or pelvic floor muscle training, have also shown promising results, although to the best of the knowledge of the authors of the current study, there has been no study of behavioral treatment of insomnia focused on nocturia as an outcome. A recently completed sleep study provided an opportunity to evaluate changes in nocturia in older adults receiving brief behavioral treatment of insomnia (BBTI).…”
mentioning
confidence: 90%
“…The recommended treatment of nocturia in older adults includes optimizing therapy for fluid overload conditions such as congestive heart failure and diabetes mellitus and treating underlying bladder or prostate etiologies with antimuscarinics or alpha‐blockers, but such agents cause adverse events and further enhance the risk of falls, fractures, and mortality in older individuals with nocturia . Multicomponent behavioral or lifestyle interventions to improve nocturia, mostly focused on fluid restriction, preemptive voiding, or pelvic floor muscle training, have also shown promising results, although to the best of the knowledge of the authors of the current study, there has been no study of behavioral treatment of insomnia focused on nocturia as an outcome. A recently completed sleep study provided an opportunity to evaluate changes in nocturia in older adults receiving brief behavioral treatment of insomnia (BBTI).…”
mentioning
confidence: 90%
“…), medication timing (diuretics in the midafternoon), evening leg elevation to mobilize fluids, use of sleep medications or sleep aides, and use of protective undergarments [2]. Although no randomized controlled trials (RCTs) evaluating the effect of behavioral modification on nocturia as a primary outcome have been found, one study showed that the education about life style modification could reduce nocturia episode and related quality of life [17]. …”
Section: Managementmentioning
confidence: 99%
“…Current data on the therapy of nocturia support this notion. A study examining the effects of behavioral therapy, including evening fluid restriction, demonstrated a significant decrease in nocturic episodes and an average reduction of 106 ml in nocturnal urine volume, after two behavioral modification education sessions [20]. In contrast, a recent study showed mirabegron to have increased voided volume by 11 ml/void relative to placebo [21].…”
Section: Discussionmentioning
confidence: 99%